Do Some Forms of Financial Flows Help Protect From Sudden Stops? - Mauro, Paolo (International Monetary Fund, 2006)
There is a debate on whether some forms of financial flows offer better crisis protection than others. Using a large panel of advanced, emerging, and developing countries during 1970-2003, this paper analyzes the behavior of various types of flows: foreign direct investment (FDI), portfolio equity investment, portfolio debt investment, other flows to the official sector, other flows to banks, and other flows to the non-bank private sector. Differences across types of flows are limited with respect to volatility, persistence, cross-country comovement, and correlation with growth at home or in the world economy. However, consistent with conventional wisdom, FDI is found to be the least volatile form of financial flows when taking into account the average size of net or gross flows. The differences are striking during ""sudden stops"" in financial flows (defined as drops in total net financial inflows by more than 5 percentage points of GDP compared with the previous year): in such episodes, FDI is remarkably stable; portfolio equity also seems to play a limited role; portfolio debt experiences a reversal, though it recovers relatively quickly; and other flows (including bank loans and trade credit) experience severe drops and remain depressed for a few years